Carbon Dioxide Dry Reforming over Molybdenum Oxide Supported Nickel-Cerium Catalyst To Produce Synthesis Gas - A/L M. Elanjaran, Yuwerajen Mohan (IRC, 2016)
The process of carbon dioxide dry reforming to produce syngas has received a wide reception in recent times. However, one of the major problem in this process is the catalyst activity is attributed to the high thermodynamic potential towards coke formation and sintering. The most appropriate catalyst and its support needed to be selected to ensure that the supported catalysts possess high activity, selectivity, longer lifetime and thermal stability in order to give the best yield of syngas. Thus, the objective of this project is to prepare molybdenum oxide supported nickel-cerium catalyst through wet impregnation method for carbon dioxide dry reforming process to produce synthesis gas and to investigate its performance based on physiochemical characterization. The methodology for this project is divided into three parts, where the first is to prepare the needed reagent and materials, followed by preparation of the catalyst and lastly is catalyst activity test. The results are taken based on the Gas Chromatography Analysis and BET surface area analysis to discuss on the effectiveness of the catalyst on the CO2 dry reforming process